If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+5x-6+2x=-4(x-3)+7
We simplify the equation to the form, which is simple to understand
3+5x-6+2x=-4(x-3)+7
Reorder the terms in parentheses
3+5x-6+2x=+(-4x+12)+7
Remove unnecessary parentheses
+3+5x-6+2x=-4x+12+7
We move all terms containing x to the left and all other terms to the right.
+5x+2x+4x=+12+7-3+6
We simplify left and right side of the equation.
+11x=+22
We divide both sides of the equation by 11 to get x.
x=2
| 36=-44+a | | .5(6x-8)=1.4(x-5)-.2 | | 36=-44+2 | | 0=6u-31 | | 0=6u-31 | | 11=-12+c | | 5h-12=4h+7 | | -8x+29=-7x | | 3=11+a | | .7(3x-5)+3.9x=14.5 | | 1-10x=91 | | 6x-12=8x-9 | | 2x-1=+11 | | -46-14n=-8(-6b+1) | | 3d+3c+5c= | | (7a+3)+(-a-5)=14 | | 9x^2-6x+6=0 | | -7(x+1)+(14x)=7(x+3)-14 | | 2/3(x+5)=4/9 | | 2m^2+10m=-12 | | 130-7x=38x+20 | | 32w^3-2v^4w^3=0 | | x^3-2x^2-9x-2=0 | | 27.5=2.5q+1q-4 | | 4(x+2)-2(x-4)=32 | | y+3=24 | | n+35=46 | | X^3-27=y | | 6-8x=8x+22 | | 3-0.5x=-2 | | 2x+15=44+8x | | 6-2(3x-1)+2=2 |